(3x/5)-7=(2x/6)+1

Simple and best practice solution for (3x/5)-7=(2x/6)+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x/5)-7=(2x/6)+1 equation:


(3x/5)-7=(2x/6)+1

We simplify the equation to the form, which is simple to understand
(3x/5)-7=(2x/6)+1

Remove unnecessary parentheses
+ 0.6x-7=( + 0.33333333333333x)+1

Remove unnecessary parentheses
+ 0.6x-7=0.33333333333333x+1

We move all terms containing x to the left and all other terms to the right.
+ 0.6x-0.33333333333333x=+1+7

We simplify left and right side of the equation.
+ 0.26666666666667x=+8

We divide both sides of the equation by 0.26666666666667 to get x.
x=30

See similar equations:

| 72y^3/64y^7 | | a-3.95=1.5 | | 55=(9-d)11 | | 4+7y=10 | | mx^2-(m-3)x+4m=0 | | -19+x=x+22 | | -8x+4=-26x | | 5(x+2.5)=4x-7.5 | | 16(3x-8)=4(12x+2) | | 4x^2+20=24x | | 7(k+m)=7k+7m | | 4(2x+5)=2(3x+5) | | (6+u)(4u-9)= | | x*2+12x-2=0 | | y+4=(x+2) | | 279.6z+10=79.9 | | 4x^2-17xy+15y^2= | | 8.2y+5=9.1 | | 4x^2+8x+35=0 | | 149.4x+3=77.7 | | 11(v+2)-2v=3(3v+1)-12 | | 7(3x+1)=2(2x+4) | | 5sinx-1=0 | | 563.5y-97.7=15 | | 5v^2+6-2v^2+v+7= | | 103.2x-17.8=8 | | 3x^5+10x^4+10x^3-5x-1=0 | | x-2=y/2 | | -8u+14=-2(u-1) | | -(18/(-6))-12= | | 2/n=5/30 | | -12-18/(-6) |

Equations solver categories